Methodology of Transport Scheme Selection for Metro Trains Using a Combined Simulation-Optimization Model - Stoilova, Svetla Dimitrova; Stoev, Veselin Valentinov (Promet - Traffic&Transportation, 2017)
A major problem connected with planning the organization of trains in metros is the optimization of the scheme of movement, which determines the routing and the number of trains. In this paper, a combined simulation-optimization model including four steps is proposed. In the first step, the train movement has been simulated in order to study the interval between the trains according to the incoming passenger flows at the stations. The simulation model was elaborated using the ARENA software. The results were validated through experimental observations. Using the results obtained from simulations in the second step the correlation between the observed parameters - the incoming passengers and the interval between trains - has been studied. Recent research has established a non-linear relationship between the interval of movement, incoming passengers at the station and passengers on the platform. The third step defines the variant schemes of transportation. The fourth step presents the optimal choice of transportation of trains in metros based on linear optimization model. The model uses the regression obtained in the second step. The practicability of the combined simulation-optimization model is demonstrated through the case study of Sofia’s metro in two peak periods – morning and evening. The model results and the real situation have been compared. It was found that the model results are similar to the real data for the morning peak period but for the evening peak period it is necessary to increase the number of trains.